2001
DOI: 10.1590/s0074-02762001000700018
|View full text |Cite
|
Sign up to set email alerts
|

Leishmanial antigens in the diagnosis of active lesions and ancient scars of American tegumentary leishmaniasis patients

Abstract: Cutaneous biopsies (n = 94) obtained from 88 patients with American tegumentary leishmaniasis were studied by conventional and immunohistochemical techniques. Specimens were distributed as active lesions of cutaneous leishmaniasis (n = 53) (Group I), cicatricial lesions of cutaneous leishmaniasis (n = 35) (Group II) and suggestive scars of healed mucosal leishmaniasis patients (n = 6) (Group III). In addition, active cutaneous lesions of other etiology (n = 24) (Group C1) and cutaneous scars not related to lei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 42 publications
3
52
0
3
Order By: Relevance
“…In spite of that, the MST remains positive before and after treatment, and therefore, the MST response is independent from the treatment 8 , although we cannot be certain about the changes of the MST intensity after treatment, as this has not been measured by the authors. In comparison with in vitro studies, the treatment does not change the immunological response of the patients with LCL, as demonstrated by some authors 1,13,30 . DA-CRUZ et al 13 demonstrated in peripheral blood of patients with localized cutaneous leishmaniasis caused by L. braziliensis, that the type of cytokine remains the same, i.e., the Th1 type, before and after the treatment.…”
Section: Discussionmentioning
confidence: 70%
“…In spite of that, the MST remains positive before and after treatment, and therefore, the MST response is independent from the treatment 8 , although we cannot be certain about the changes of the MST intensity after treatment, as this has not been measured by the authors. In comparison with in vitro studies, the treatment does not change the immunological response of the patients with LCL, as demonstrated by some authors 1,13,30 . DA-CRUZ et al 13 demonstrated in peripheral blood of patients with localized cutaneous leishmaniasis caused by L. braziliensis, that the type of cytokine remains the same, i.e., the Th1 type, before and after the treatment.…”
Section: Discussionmentioning
confidence: 70%
“…Some authors [13,15] report mixed infections in areas where these protozoa coexist. Crossreactivity was also observed among antigens of Leishmania and antibodies of people bearing deep mycoses, when these diseases share the same transmission area [16,17]. There were unspecified reactions with antibodies of people without leishmaniasis or carriers of other pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Parasite identification is difficult and sensitivity reports vary with different techniques, from 0.2% with direct smear to 68.6% when various methods are used (Weigle et al 1987, Zajtchuk et al 1989, Schubach et al 2001, Disch et al 2005. In cases where there is a strong clinical suspicion and no parasite is isolated, treatment is prescribed with pentavalent antimony which is highly effective, but has been associated with frequent adverse effects: malaise, headache, muscle pain, joint pain and hepatic, pancreatic, renal, hematologic, and cardiac toxicity that has lead to death in some cases (Chulay et al 1985, Hepburn et al 1994, Aronson et al 1998.…”
Section: ) the Inter-observer Agreement Was Excellent For Both Testsmentioning
confidence: 99%